Comparison of Human Papillomavirus Detection between Freshly Frozen Tissue and Paraffin Embedded Tissue of Invasive Cervical Cancer - Odida, Michael; Sanjose, Silvia de; Quiros, Beatriz; Alemany, Laia; Lloveras, Belen; Alejo, Maria; Weiderpass, Elisabete (Infectious agents and cancer, 2010)
Human Papillomavirus (HPV) detection results comparing paraffin embedded cervical tissue and other cervical specimens have been done with varying degrees of agreement. However, studies comparing freshly frozen specimens and paraffin embedded specimens of invasive cervical carcinomas are lacking. The aim of the study was to compare HPV detection using SPF10 broad-spectrum primers PCR followed by DEIA and genotyping by LiPA25 (version 1) between freshly frozen cervical tissue samples and paraffin embedded blocks of cervical tissue from the same patient. There were 171 pairs of paraffin embedded and freshly frozen samples analyzed from cervical carcinoma cases from Kampala, Uganda.
Keywords: Paraffin Block; Paraffin Embed Tissue; Formalin Fixed Paraffin Embed; Invasive Cervical Carcinoma